ANALYSIS OF NURSING CARE IN STROKE PATIENTS WITH THE PROVISION OF ELEVATION HEAD POSITION TO OVERCOME NURSING PROBLEM RISK OF INEFFECTIVE CEREBRAL PERFUSION AT RSI SURABAYA A. YANI - Nur Hamidah Maghfiro; Wardani, Erika Martining; Rusdianingseh; Muhith, Abdul (Universitas Nahdlatul Ulama Surabaya, 2024)
Introduction: Stroke treatment must be done quickly and precisely because the longer the stroke is not treated immediately, the higher the severity of the stroke. One of the complications of stroke is cerebral circulation disorders which cause several symptoms including cerebral tissue hypoxia. Objective: This study aimed to analyze nursing care for stroke patients by giving elevated head positions to overcome the nursing problem risk of ineffective cerebral perfusion at RSI Surabaya A. Yani. Methods: This research design is a case study with Mrs. M who has nursing problems at risk of ineffective cerebral perfusion. Data collection was done directly by interview, observation, and physical examination of Mrs. M and her family directly. Nursing interventions for providing elevated head positions are carried out for three days for 30 minutes daily. Results: The results showed that after implementation there was a significant increase in oxygen saturation in Mrs. M on the first day SpO2 95%, on the second day SpO2 97%, and on the third day SpO2 99%. In addition to an increase in oxygen saturation, there was an increase in the outcome criteria to be achieved, namely the level of consciousness on a scale of 4 (moderately improved), headache on a scale of 4 (moderately decreased), average blood pressure values on a scale of 4 (moderately improved), and awareness on a scale of 4 (moderately improved). Conclusions: Giving an elevated head position is effective in increasing oxygen saturation in stroke patients with nursing problems of ineffective cerebral perfusion risk. Room nurses can perform elevation head positioning to improve oxygen saturation in stroke patients with nursing problems at risk of ineffective cerebral perfusion.